KORELASI ANTARA ANSIETAS, DEPRESI, DAN DUKUNGAN SOSIAL DENGAN AKTIVITAS PERAWATAN DIRI KLIEN DIABETES MELLITUS TIPE 2 - Simamora, Febrina Angraini (Jurnal Kesehatan Ilmiah Indonesia (Indonesian Health Scientific Journal), 2016)
Diabetes self-care is a program or an action that has to be done for the rest of the clients’ life and is the responsibility of the diabetes clients. Individuals with Type 2 diabetes must comply with the tasks of self-care in order to achieve the optimal blood sugar control. This research was aimed at identifying the correlation among anxiety, depression, and social support with self care activity. Moreover, descriptive correlation was applied as the design of this research. There were 62 people taken as the sample by using purposive sampling technique. The data were acquired through questionnaires and blood sugar check up. Then they were analyzed by Chi-square test. The results of this research showed that there was a relationship among anxiety, depression, and social support with the Type 2 diabetes clients’ self-care activity. The clients with Type 2 diabetes who are in good psychosocial condition would be able to perform self-care-\activity so that they would be able to control the blood sugar. The Type 2 diabetes clients were hoped to be able in adaptation with their diabetes, so they haven’t anxiety and depression, and then they can do their self care activities and can control their blood sugar.